Letter (copy) : Senor Pascual Tomas - Citrine, Walter, 1887-1983
026-0069-001 International. WMC/EAB/AT/1005 PRIVATE 16th June, 1939. The Rt. Hon. Viscount Halifax, K.G., G.C.S.I., G.C.I.E., T.D., Foreign Secretary, Whitehall, S.W.1. Dear Lord Halifax, SENOR PASCUAL TOMAS I have your letter of the 15th instant, informing us that you have heard from the British Consul at Valencia that he has been able to visit Dona Carmen Belloque Amargos, wife of Sr. Pascual Tomas, and her three daughters in Valencia. I am very grateful indeed for the action you have taken and I know that the assurance that his wife and daughters are all well will relieve Sr. Tomas from much anxiety. I can quite appreciate the impossibility at this stage of arranging for these people to leave Spain, but I do sincerely hope that it will be possible to do something in this direction in the near future. Again thanking you for your very kind assistance, I am, Yours sincerely, General Secretary. 292/946/26/69